Analysis of Health Service Queues at BP Umum Puskesmas X Using Promodel Simulation - Tombak Gapura Bhagya; Antari Nurayban Gitardiana; Dini Yulianti; Ida Bagus Indria Swarnandhika (Sainteks: Jurnal Sain dan Teknik, 2022)
Puskesmas is a health service center in Indonesia that serves the community in the closest scale. Almost all people in Indonesia today, if they want to do treatment or referrals, they must go to the puskesmas. So this study tries to analyze the services of the puskesmas and evaluate the queues in the puskesmas using the Promodel simulation. Simulation is considered as a suitable tool for analyzing service queues at puskesmas. The results of this study indicate the need to increase the number of doctors to 2 to 3 people to reduce the number of queues that accumulate waiting to be examined by a doctor. If the additional doctor points cannot be met, then the puskesmas can provide adequate waiting room facilities for patients to be examined by a doctor, the ideal number of waiting room seats for patients waiting to be examined by a doctor is 38 seats.